Therapeutic Potential of Withania somnifera on Nandrolone Decanoate Induced Gonadal Toxicity - Sivanandam, Sugumaran; Senthilkumar, Sivanesan; Dipti, Boopalan; Subashree, Ravishankar Priyadarsini; Visakha, Vinod; Praveenkumar, Parthiban (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Nandrolone decanoate (ND) is a commonly used androgen-based steroid that causes adverse effects on illicit self-administered users to boost their physical endurance. Although, it has an anabolic effect on the skeletal muscles, plausible evidence supports that the gonadal toxicity of ND can cause damage to reproductive functions. Aim: The present study investigated the possible protective effects of Withania somnifera (WS) root extract (200 and 400 mg/kg bw) on ND-induced (10 mg/kg bw) male gonadal toxicity in rats. Materials and Methods: The present seminal research was not experimented in any of the earlier studies. ND was induced in rats by intramuscular injection bi-weekly for 30 days. The aqueous extract of WS root powder was delivered orally once daily for 30 days to the ND-treated group. Hematoxylin-and-eosin-marked sections of the testes were studied. Results: The testosterone levels significantly decreased while there was an increase in the malondialdehyde levels among the ND-induced group against the control group. The ND induced rats treated with varying doses of WS showed a significant reversal of the gonadal toxicity by improvement in the testosterone and antioxidant parameters. The sperm count and sperm motility rate were increased significantly after WS therapy. Furthermore, the testis morphology of the WS-treated group indicated preserved germinal cells, active spermatogenesis, and absence of atrophy, vacuolation, and necrosis. Conclusion: WS treatment in ND-induced male rats alleviated the toxic effects of the ND on the gonads, probably due to its anti-inflammatory and antioxidant properties.
Keywords: Nandrolone decanoate; Withania somnifera; Gonadal toxicity; Testosterone; Sperm; count; Sperm motility